Geologi Blok “X” di Kampung Klasari, Kabupaten Sorong, Provinsi Papua Barat Daya - Zulsusiana Lahmuda; Yayu Indriati Arifin; Muhammad Kasim (Universitas Negeri Gorontalo, 2026)
This study discusses the geological condition of Block “X” in Kampung Klasari, Moi Segen District, Sorong Regency, Southwest Papua Province. The article follows the structure of a regional geological study by focusing on geomorphology, and stratigraphy. The methods used include surface geological mapping, interpretation of topographic and geological maps, lithological observation, and descriptive analysis of field photographs. The results show that the geomorphology of the study area is divided into two units, namely a flat lowland unit and a swamp plain subunit. Stratigraphically, the area is composed of the Sele Claystone Unit, Sele Sandstone Unit, local coal occurrence, and Quaternary alluvial deposits. The relationship between morphology, sedimentary lithology, and fluvial.